Waterbird Foraging Habitat Selection in Balikpapan Bay: Water Depth and Patch Area as Important Factors - Alexander Kurniawan Sariyanto Putera; Dyah Perwitasari-Farajallah; Yeni Aryati Mulyani; Stanislav Lhota; Riki Herliansyah; Sodikin Sodikin (HAYATI Journal of Biosciences, 2021)
Balikpapan Bay is one of the wetlands providing potential foraging habitat for waterbirds in Indonesia. Potential habitat loss due to oil industry expansion, recent waterbird occurrence, and co-occurrence of two closely related species with similar foraging characteristics led to habitat selection. Habitat selection could be affected by food as an intrinsic factor and extrinsic factor, for example, accessibility to the physical and biological components of the habitat. This study aimed to measure the foraging habitat selection, identify significant habitat quality parameters for the habitat selection and predict the foraging habitat selection model. We used one-zero sampling for collecting foraging habitat selection data, corer sampling for prey data, and collecting the abiotic environment, and Generalized Linear Modelling (GLM) to build the model. We identified four species as the migrant Little Egret (Egretta garzetta), Great Egret (Ardea alba), Purple Heron (Ardea purpurea), and Lesser Adjutant (Leptoptilos javanicus). All species, except Purple Heron, selected foraging habitats. A simple mathematic model of foraging habitat selection was significantly affected by two factors: water depth and patch area. A large patch area may provide primary prey abundance for waterbirds, while a low water depth level may give easy access to the prey.